Computer Hexapod–Assisted Orthopaedic Surgery for the Correction of Tibial Deformities. Issue 7 (July 2016) - Hughes, Andrew; Parry, Michael; Heidari, Nima; Jackson, Mark; Atkins, Roger; Monsell, Fergal
Abstract : Summary: We describe the intraoperative use of the Taylor Spatial Frame to correct complex multiplanar deformities of the tibia before definitive internal stabilization using minimally invasive techniques. Thirteen consecutive procedures were performed in 12 patients. All deformities of the tibia were assessed with standardized radiographs allowing estimation of the center of rotation of angulation (CORA) or multiple CORA for multiplanar deformities. The cause of the deformity included both posttraumatic and metabolic conditions. A wide range of deformities was deemed appropriate for correction with this technique. All underwent acute intraoperative correction through single or multiple osteotomies mediated by the Taylor Spatial Frame before definitive internal stabilization using a locked intramedullary nail. Deformity correction and restoration of the tibial mechanical axis was achieved in all cases. There were no cases of nonunion. There was only one superficial infection necessitating removal of implants following union of the osteotomies. Two patients developed a common peroneal nerve palsy, 1 had full recovery at 18 months and 1 had partial recovery. Another patient developed a tibial artery pseudoaneurysm treated successfully with a percutaneous stent. This series demonstrates the use of the Taylor Spatial Frame for acute intraoperative correction of complex tibial deformities and definitive internal stabilization. Abstract : Supplemental Digital Content is Available in the Text.